Alterations in energy metabolism during exercise and heat stress - Febbraio, M. A. (Sports Medicine, 2001)
Much of the research that has examined the interaction between metabolism and exercise has been conducted in comfortable ambient conditions. It is clear, however, that environmental temperature, particularly extreme heat, is a major practical issue one must consider when examining muscle energy metabolism. When exercise is conducted in very high ambient temperatures, the gradient for heat dissipation is significantly reduced which results in changes to thermoregulatory mechanisms designed to promote body heat loss. This can ultimately impact upon hormonal and metabolic responses to exercise which act to alter substrate utilisation. In general, the literature examining metabolic responses to exercise and heat stress has demonstrated a shift towards increased carbohydrate use and decreased fat use. Although glucose production appears to be augmented during exercise in the heat, glucose disposal and utilisation appears to be unaltered. In contrast, glycogen use has been consistently demonstrated to be augmented during exercise in the heat. This increase in glycogenolysis is observed via both aerobic and anaerobic pathways. Although several hypotheses have been proposed as mechanisms for the substrate shift towards greater carbohydrate metabolism during exercise and heat stress, recent work suggests that an augmented sympatho-adrenal response and intramuscular temperature may be responsible for such a phenomenon.